Optimal power allocation for a hybrid energy harvesting transmitter - Ahmed, Imtiaz; Ikhled, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications, 2013)
In this work, we consider a point-to-point link where the transmitter has a hybrid supply of energy, i.e., the energy is supplied by a constant energy source and an energy harvester, which harvests energy from its surrounding environment. Our goal is to jointly minimize the power consumed by the constant energy source and any possible waste of the harvested energy to ensure their optimum utilization for transmission of a given amount of data in a given number of time intervals. Two scenarios are considered for packet arrival. In the first scenario, we assume that all data packets have arrived before the transmission begins, whereas in the second scenario, we assume that data packets are arriving during the course of data transmission. For both scenarios, we propose optimal offline transmit power allocation schemes which provide insight on how to efficiently consume the energy supplied by the constant energy source and the energy harvester. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03